Jump performance progression in spanish male and female elite high and long jumpers - Rodríguez-gómez, P.; Gallo-salazar, C.; Salinero, J. J. (International Journal of Performance Analysis in Sport, 2025)
Objective This study analysed the evolution of high jump and long jump performance by male and female athletes across age categories (under-14 to senior) over a longitudinal period.